The CoCoME platform: a research note on empirical studies in information system evolution - Heinrich, Robert; Hesse, Tom-Michael; Paech, Barbara (International journal of software engineering and knowledge engineering, 2015)
Methods for supporting evolution of software-intensive systems are a competitive edge in software engineering as software is often operated over decades. Empirical research is useful to validate the effectiveness of these methods. However, empirical studies on software evolution are rarely comprehensive and hardly replicable. Collaboration may prevent these shortcomings. We designed CoCoMEP — a platform for supporting collaboration in empirical research on software evolution by shared knowledge. We report lessons learned from the application of the platform in a large research programme.